Relationship between Brand Value, Firm Size and Stock Price Performance: 2nd Generation Panel Data Analysis on Turkish Retail Sector and Sport Clubs - Özyeşil, Mustafa (International Journal of Economics and Financial Issues, 2019)
In this study, the effect of brand value and asset size on stock price performance is examined. For this purpose, data of 7 listed companies that operate in the retail and sports sectors whose shares have been traded on the Borsa Istanbul (BIST) during the 2012-2018 period were used. In this study, the effect of brand value and asset size on stock price performance is analyzed through using 2nd Generation Panel Data Analysis Methods. The existence of cross-sectional dependency among the firms was analyzed by LMBC test. Based on the findings of this test, the existence of cross-sectional dependence among these firms was determined. Stationarity of the series was examined by HK panel unit root test and it was decided that all series were stationary in the first difference. Homogeneity of slope coefficients was examined by Delta test and it was decided that slope coefficients to be estimated in this study were homogeneous. The existence of cointegration relationship between the series was examined by ECM cointegration test. According to the results of the cointegration test, it was decided that there is a cointegration relationship between the series in the econometric model. The coefficients included in the econometric model were determined by using OLSAdj method. According to the results of the model, when the brand value of the firms in the sample increased by 1%, the prices of stocks responded to this by increasing by 2.21%. Similarly, when the asset size of these firms increased by 1%, stock prices increased by an average of 3.21%. Therefore, it can be concluded that asset size has more effect on stock price performance than brand value. Keywords: Stock Price Performance, Brand Value, Asset Size, 2nd Generation Panel Data Analysis JEL Classifications: E44, H32, L25. DOI: https://doi.org/10.32479/ijefi.8470